Severe Generalized Sweet Syndrome with good outcome: A Case Report - Vargu, Migena; Vargu, Petrit; Dedej, Sabina; Kurushi, Eriselda; Vargu, Samuele; Anyim, Alecia; Mensah, Elsie Tachie; Gowaily, Ibrahim; Tan-Wohlers, Jaclyn; Lin, Grace; et al. (Archives of Clinical and Biomedical Research, 2025)
Sweet syndrome (SS), also known as acute febrile neutrophilic dermatosis, is characterized by fever, elevated white blood cell counts predominantly composed of neutrophils, painful red plaques on the skin, and dermal neutrophilic infiltration without vasculitis. SS can be triggered by various factors and is diagnosed based on clinical, laboratory, and histopathological criteria. SS is classified into three types: classical (or idiopathic), malignancy-associated, and drug-induced. Classical Sweet syndrome is the most common form, often linked to infectious diseases, inflammatory disorders, or pregnancy. This case report describes a patient with an aggravated and generalized form of Sweet syndrome who had a favorable outcome following appropriate treatment.